Effective leadership for overcoming ICT challenges in higher education : what faculty, staff and administrators can do to thrive amidst the chaos - Carbonaro, Antonella; Breen, Jennifer Moss (Emerald Publishing Limited, 2021)
Although it is vital that the incorporation of ICT into academic culture is effective and lasting, the very nature of higher education, with its long ties to tradition and academic values, does not lend itself easily to emerging ICT strategies. This book asks how we, as educators, can shift mind-sets, practices, policies, and attitudes in higher education in order to serve society and meet the educational needs of today. Tackling the critical question of how to manage knowledge for value creation in the higher education environment, the authors draw attention to smart ICT use for knowledge creation and sharing. Serving up a mixture of case studies, examples, questions and tools, they also deliver insights on the human element involved in both ICT and higher education. By providing a conceptual model for implementing Knowledge 4.0 in educational environments, this book ultimately facilitates a dialogue within higher education institutions that brings forth emerging practices and examples of cultural adaptation. Confronting the idea that innovation brings chaos to institutions steeped in tradition, this edited collection is a must-have guide for those interested effecting technological change in educational environments while also sustaining academic quality and delivering meaningful learning outcomes.
Includes index.
Keywords: Educational leadership.; Education, Higher -- Information technology.; Communication in higher education.; Education -- Computers & Technology.; Educational equipment & technology, computer-aided learning (CAL).; elektronické knihy; electronic books